Research in Costa Rica involving human beings and its impact of on the health of costa ricans - Granados Zúñiga, Jorge (2013)
We evaluate the benefits of clinical research carried out in Costa Rica from the published results and a sample of informed consent forms of approved protocols. We found 30 studies on 28 pharmaceuticals and 23 published scientific papers. Results: Of surveyed medical conditions, 19% are directly related to the main causes of mortality and morbidity in our country does not seem to have been necessary for drug registration.  A placebo as control was ued in 27% of investigations; of all studies with results, 30% had not published results, 37% published positive results, 17% ambiguous or contradictory results and 13% ended prematurely. Out of the major authors responsible for the publications, 91% were affiliated with research centers abroad. Conclusions: We conclude that there is insufficient evidence to claim  that analyzed clinical research has provided a significant benefit to the health of Costa Ricans, represents a significant therapeutic option, or has provided a significant contribution to scientific research in Costa Rica.